Spontaneous Subarachnoid Haemorrhage in Neurological Setting in Burkina Faso: Clinical Profile, Causes, and Mortality Risk Factors - Alfred Anselme Dabilgou; Alassane Drave; Julie Marie Adeline Kyelem; Lanseni Naon; Christian Napon; Jean Kabore (Neurology Research International)
To determine the prevalence, clinical profile, causes, and mortality risk factors of spontaneous arachnoid haemorrhage at Yalgado Ouedraogo University teaching Hospital, we conducted a 5-year retrospective study of 1803 stroke patients admitted to Neurology Department during the period from January 2012 to December 2016. During the study period, spontaneous subarachnoid haemorrhage accounted for 3.2 % of all stroke. The mean age of patients was 60 years (range 20-93 years). There was a female predominance in 55.9%. The common vascular risk factors were hypertension (79.7%) and chronic alcohol consumption (16.9%). The main symptoms were headache (76.2%), motor weakness (74.5%), and consciousness disorders (62.7%). Neurological examination revealed limb weakness in 76.2% and meningeal irritation in 47.4%. The best admission Glasgow Coma Scale score of 15 was found only in 37.3 % of patients. About 50.8% of patients were admitted to Hunt and Hess moderate grade (III) resulting in a mortality of 24.80%. The main cause of spontaneous subarachnoid haemorrhage was hypertension (77.9%). Cause could not be determined in 8.5 % of cases. The mortality rate was 37.3%. There was high mortality in patients with intraventricular haemorrhage and in patients with disturbances of consciousness. In conclusion, our study showed a poor frequency of spontaneous subarachnoid haemorrhage with high mortality. Hypertension was the most common cause of spontaneous subarachnoid haemorrhage.